Biomasa de especies comerciales en un bosque de colina baja aplicando ecuaciones alométricas. Jenaro Herrera, Loreto, Perú – 2023 - Chávez Ramírez, Erika Jacqueline (2024)
This study used allometric equations to evaluate the biomass of commercial species in a low hill forest in the area of Jenaro Herrera, Loreto, Peru. Data from the forest census of commercial species from the private property “El Aguajal” were evaluated. Six botanical groups and eight commercial forest species make up the floristic mix; a total of 64 trees were observed. There are 3.94 trees per hectare. Macrolobium angustifolium (0,92) and Allantoma decandra (1,05 trees/ha) have the most trees. The correlation between DBH and commercial height is -0,167. There is a regular and negative relationship. After fitting the quadratic allometric model (Y= 33,326 + (0,569 * DBH) + (0,004 * DBH2) to the association between DBH and commercial height, r= 0,942 and R2= 0,888 were obtained. The total dry biomass of commercial forest species is 26 262,68 kg/ha. Allantoma decandra has the highest biomass with 5866,31 kg/ha, followed by Macrolobium angustifolium with 3969,54 kg/ha.